2020
DOI: 10.1016/j.ijrobp.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Whole-Lung Irradiation for COVID-19 Pneumonia: Short Course Results

Abstract: The COVID-19 outbreak is affecting people worldwide. Many infected patients have respiratory involvement that may progress to acute respiratory distress syndrome. This pilot study aimed to evaluate the clinical efficacy of low-dose whole-lung radiation therapy in patients with COVID-19 pneumonia. Methods and Materials: In this clinical trial, conducted in Iran, we enrolled patients with COVID-19 who were older than 60 years and hospitalized to receive supplementary oxygen for their documented pneumonia. Partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 12 publications
7
54
0
Order By: Relevance
“…Our data show that low doses of RT decrease the tissue damages in the infected mice, and will contribute to define the optimal radiation dose to be used in the clinic, which is the minimal dose to induce a maximal impact on macrophage reprogramming without tissue damages, our data suggest that the 0.5-1Gy range should be considered clinically. In line with our data, several clinical studies including COVID-19 presenting pneumonia patients with advanced age or comorbidities reported an absence of acute toxicity after whole thorax low doses of RT (8, 9). In these clinical studies, the authors reported an improvement in the respiratory function of the patients in the hours following low doses of RT with a marked improvement on the CT scan around 7 days after RT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data show that low doses of RT decrease the tissue damages in the infected mice, and will contribute to define the optimal radiation dose to be used in the clinic, which is the minimal dose to induce a maximal impact on macrophage reprogramming without tissue damages, our data suggest that the 0.5-1Gy range should be considered clinically. In line with our data, several clinical studies including COVID-19 presenting pneumonia patients with advanced age or comorbidities reported an absence of acute toxicity after whole thorax low doses of RT (8, 9). In these clinical studies, the authors reported an improvement in the respiratory function of the patients in the hours following low doses of RT with a marked improvement on the CT scan around 7 days after RT.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical reports suggest an early improvement of breathing difficulties within hours and a reduction of mortality (5–7). Currently, several clinical trials are underway (referenced on clinicaltrial.gov) and some studies, even if in small cohorts, confirmed the efficacy of low doses of RT in the treatment of ARDS in patients with severe COVID-19 (810). However, the involved mechanisms remain unknown and the use of chest radiation therapy (RT) for COVID patients has been the subject of a vivid scientific controversy.…”
Section: Introductionmentioning
confidence: 99%
“…One question, evaluated in the current study by Hess et al, 1 is the risk of RT worsening acute symptomatology. This was not apparent in at least 4 of the 5 patients treated by Hess et al and is encouraging, as were the similar findings in the results reported by Ameri et al 1,18 This does not completely rule out worsening of acute symptoms by LD‐RT in a subset of patients, but does provide a degree of comfort as these and similar trials continue to accrue.…”
Section: Rationalesupporting
confidence: 71%
“…As of this writing, 9 trials addressing this question are listed as recruiting on the ClinicalTrials.gov website, with 4 being performed in the United States, including the study by Hess et al in this issue of Cancer 1 . Indeed, the results of a separate trial recently were published by Ameri et al using LD‐RT at a dose of 0.5 Gy, with similar findings reported 18 . Specifically, clinical recovery was reported in 3 of 4 patients, with 1 patient dying of COVID‐19.…”
Section: Rationalementioning
confidence: 81%
“…There are currently fifteen prospective studies being carried out to assess the role of low dose RT in COVID-19 patients. The first results of two trials have just been published and have shown promising results (Ameri et al 2020;Hess et al 2020). However, a careful interpretation is required as they are based on very small participant numbers (n ¼ 5, n ¼ 5), are non-randomized, and have no control groups.…”
Section: Introductionmentioning
confidence: 99%